Investigation of Single and Paired Measurements of Adrenocorticotropic Hormone for the Diagnosis of Pituitary Pars Intermedia Dysfunction in Horses. (13th October 2014) - Rendle, D.I.; Duz, M.; Beech, J.; Parkin, T.; Durham, A.E.
<x xml:space="preserve">Abstract</x> Background Paired measurement of ACTH concentration may be more reliable than a single measurement. Hypothesis/Objectives To determine whether the mean of 2 measurements of ACTH concentration is more reliable in assessing pituitary pars intermedia dysfunction (PPID) than a single measurement. Animals Paired ACTH measurements were performed on (1) 148 occasions from 124 horses being investigated for PPID, (2) 90 occasions from 76 horses with PPID that were receiving treatment with pergolide, and (3) 63 occasions from 50 horses in which there was no clinical suspicion of PPID. Histologic examination of the pars intermedia was performed in 67 of the untreated horses. Methods Outcome of testing using single and the mean of paired samples was compared directly and both methods were compared against histology, which was considered the gold standard. Results Paired ACTH measurement altered binary classification as healthy or diseased in 6 of 211 cases, all off which had equivocal initial ACTH concentrations between 20 and 39 pg/mL. Using histology as the gold standard, optimal sensitivity and specificity for diagnosing PPID were 69.4 and 80.9%, respectively, for a single measurement and 72.2 and 76.2%, respectively, for paired measurements. The area under the receiver operating characteristic curve was 0.72 and 0.73 for single and paired measurements compared with histopathologic diagnosis, respectively. Conclusions and Clinical Importance Paired measurement of ACTH concentration offers no advantage over a single measurement.